Foley catheter guided by semi-rigid ureterorenoscopy in the treatment of bladder diverticulum: a case report - Wiratma, Made Kresna Yudhistira; Hendri, Ahmad Zulfan; Subekti, Eko (Faculty of Medicine, Universitas Trisakti, 2025)
Background A bladder diverticulum can be the consequence of a congenital abnormality or acquired as a result of trauma, infection, or outlet obstruction. Despite advancements in laparoscopic techniques, to date, precise intraoperative identification of diverticula remains a significant challenge. The aim of this case report was to offer an alternative technique using a foley catheter guided by semi-rigid ureterorenoscopy to facilitate bladder diverticulum identification during laparoscopic diverticulectomy. Case description A 77-year-old male patient presented with complaints of burning sensation during urination and reported frequent episodes of urinary tract infection over the past several months. Cystographic imaging revealed a large diverticulum located on the left posterior bladder wall. Non-contrast abdominal computed tomography (CT) scan identified a 10×10 mm calculus in the left inferior renal calyx. The patient was diagnosed with a bladder diverticulum. Subsequently, laparoscopic transperitoneal diverticulectomy was performed using a foley catheter guided by semi-rigid ureterorenoscopy for diverticulum identification and excision. The procedure commenced with cystoscopy to localize the diverticulum. Four trocars were inserted: two 12 mm and two 5 mm. A pneumoperitoneum pressure of 14 mmHg was maintained throughout the surgery. The diverticulum was clearly visualized during the operation, and excised successfully without injuring adjacent structures. Postoperative recovery was uneventful. Conclusion The use of a foley catheter guided by semi-rigid ureterorenoscopy may serve as an effective alternative for intraoperative identification of bladder diverticula, particularly in laparoscopic and resource-limited settings.